TRADISI ZIARAH MAKAM “DATUK RAMBAI” PADA MASYARAKAT DESA TELUK NILAP KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - ", Haryandi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The tittle in this study is "Tradition of Pilgrimage tomb Datuk Rambai In the Teluk Nilap comunity Kubu Babussalam district of Rokan Hilir". The study was conducted in the village of Kubu Babussalam in Teluk Nilap of Rokan Hilir, which aims to determine how the implementation of the pilgrimage tradition Makam Datuk Rambai and value systems that are inside. The method used in this research is descriptive qualitative research methods, that is the discussion of this study are presented and analyzed in the form of words of description (description) with a qualitative approach. This research was also supported by the implementation of in-depth interviews to sources (informants) that has been set in advance by researchers. So from the results of the interview obtained particulars were very supportive to the validity of the data that are the focus of this study. Based on the research results, in this tradition, there are several important things that is divided into two implementation pilgrimage tradition itself, namely; Pilgrimage tradition Makam Datuk Rambai in rituals starting reinforcements, as well as Pilgrimage tradition Makam Datuk Rambai in paying intention (Bernazar). Pilgrimage tradition Makam Datuk Rambai in rituals starting reinforcements carried out once in every year during the fourth day of Eid. Implementation started from 8 am until completed, with the purpose to refuse reinforcements and remove all forms of bad things and also diseases to the sea. While the tradition of pilgrimage Makam Datuk Rambai in paying intention (Bernazar) commonly carried out by people who have no intention / votive alone that are individuals or small in scope. Suppose as an example; No one from the people in the area who made a vow to the grave with the intention Datuk Rambai "If later he had recovered from his illness, he will hold a celebration of it, and will return to the tomb of Datuk Rambai to praying". Pilgrimage tradition and value systems Rambai Makam Datuk consists of several aspects depicted in History Values, Values Symbols on White Cloth, Religious Values (Religious), and Value of Kinship.Keywords: Tradition of pilgrimage, implementation, and value systems